2016
DOI: 10.1063/1.4967227
|View full text |Cite
|
Sign up to set email alerts
|

Photogenerated carriers enhancement in Cu-doped ZnSe/ZnS/L-cys self-assembled core-shell quantum dots

Abstract: The photoelectron characteristics and nano-doping mechanism of Cu-doped ZnSe/ZnS/L-cys self-assembled core-shell quantum dots (QDs) are studied by surface photovoltaic (SPV) and photoacoustic (PA) techniques, XRD, HRTEM, FT-IR, UV-VIS adsorption, and Laser Raman spectra. The results suggest that the doped copper element prefers to locate at the Zn atom-vacancy of the (111) face of the QDs in the Cu2+ ion form. The defect-state levels are referred to the shallow accepter levels, leading to an obvious quantum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Semiconductor quantum dots (QDs) are considered potential materials for light-emitting diodes (LEDs), , solar cells, , and spintronic device applications. , In the application of QD-based LEDs, the adjustable band gap and dopant energy level are deemed to be efficient and reliable solutions for versatile color purity. , Other interesting features, including a larger Stokes shift, longer excited-state lifetime, and higher thermal and chemical stability, were found by introducing transition metal ions into QDs to better control their electronic and optical properties. For example, Cu doping into Zn–In–S alloy QDs yielded wide tunable photoluminescence (PL) emission from the visible to the near-infrared . Site substitution of Cu ions in CdSe QDs was controlled by a nucleation process to tune the fluorescence emission window from blue to green .…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs) are considered potential materials for light-emitting diodes (LEDs), , solar cells, , and spintronic device applications. , In the application of QD-based LEDs, the adjustable band gap and dopant energy level are deemed to be efficient and reliable solutions for versatile color purity. , Other interesting features, including a larger Stokes shift, longer excited-state lifetime, and higher thermal and chemical stability, were found by introducing transition metal ions into QDs to better control their electronic and optical properties. For example, Cu doping into Zn–In–S alloy QDs yielded wide tunable photoluminescence (PL) emission from the visible to the near-infrared . Site substitution of Cu ions in CdSe QDs was controlled by a nucleation process to tune the fluorescence emission window from blue to green .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] In our previous works, the self-assembled core-shell CdTe/CdS/ligand, CdSe/CdS/ligand, and ZnSe/ZnS/ligand QDs were prepared via the aqueous synthesis way, respectively. [28][29][30][31] The results revealed that the ligand and the shell layer played not negligible roles in the gradual energy band structure of these QDs. For examples, the ligand not only improved the stability of the QDs, but also may change the transport mechanism and adjust the transmission channel of photogenerated free charge carriers (FCCs) in these QDs.…”
Section: Introductionmentioning
confidence: 93%
“…The incorporation of a small amount of a dopant impurity in wide bandgap semiconductors like zinc chalcogenides allows to modify the electronic states into the bandgap which provides to doped-QDs unique advantages such as minimum self-absorption due to a large Stokes shift, longer excited-state lifetime and high thermal and photostability [32][33][34]. Recently, the Cudoping of ZnS and ZnSe QDs has been investigated and it was demonstrated that the relaxation of the exciton occurs via the t2 energy states of Cu 2+ resulting in an emission in the green region valuable for applications such as bio-imaging, sensing, photocatalysis and light emitting devices [35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Gradient alloyed ZnSeS QDs are well-known to exhibit improved optical properties and higher stability compared to binary ZnS or ZnSe QDs [49][50][51][52][53] but their doping with Cu has only scarcely been investigated [54,55].…”
Section: Introductionmentioning
confidence: 99%